Recloning and Characterization of C2C12 Myoblast and Its Clonal Derivatives - Prasetyaningrum, Pekik Wiji; Septisetyani, Endah Puji; Suyoko, Ahmad; Santoso, Adi (Indonesian Journal of Cancer Chemoprevention, 2021)
The C2C12 myoblasts are adult murine muscle stem cells which isolated after injury to induce muscle regeneration. The cells are widely used in pharmaceutical and biological researches to represent skeletal muscle cells. In our laboratory, we utilize the cells for glucose uptake assay after insulin treatment and studying the muscle regeneration. In this study we conducted recloning of C2C12 cells by limiting dilution cloning (LDC) and investigated the biological properties incuding cell proliferation, adhesion and differentiation of the clonal cells in comparison to the parental cells. Cell proliferation rate had been determined by WST assay, cell adhesion had been observed after cell detachment by EDTA and cell differentiation into multinucleated myotube had been investigated after induction and incubation with horse serum. As results, two clonal derivatives of C2C12 myoblast cells had been retrieved by LDC and used for cell assays. Moreover, the results indicated that parental cells showed faster proliferation rate and better differentiation ability than that of clonal cells. In the contrary the parental cells exhibited weaker adhesion rate than clonal cells. To conclude, C2C12 parental cells are better for performing the glucose uptake or muscle regeneration assays since they showed better differentiation capability.Keywords: C2C12 cells, cells differentiation, myoblast, myotube, recloning.